Aroma profile design of wine spirits: Multi-objective optimization using response surface methodology. (15th April 2018) - Matias-Guiu, Pau; Rodríguez-Bencomo, Juan José; Pérez-Correa, José R.; López, Francisco
Highlights: High rectification during head fractions improves flowery and fruity spirit aroma. Optimal pH and distillation cuts depend on aromatic profile goal. Sensory analysis shows good correlation between aroma descriptors and chemical data. Abstract: Developing new distillation strategies can help the spirits industry to improve quality, safety and process efficiency. Batch stills equipped with a packed column and an internal partial condenser are an innovative experimental system, allowing a fast and flexible management of the rectification. In this study, the impact of four factors (heart-cut volume, head-cut volume, pH and cooling flow rate of the internal partial condenser during the head-cut fraction) on 18 major volatile compounds of Muscat spirits was optimized using response surface methodology and desirability function approaches. Results have shown that high rectification at the beginning of the heart-cut enhances the overall positive aroma compounds of the product, reducing off-flavor compounds. In contrast, optimum levels of heart-cut volume, head-cut volume and pH factors varied depending on the process goal. Finally, three optimal operational conditions (head off-flavors reduction, flowery terpenic enhancement and fruity ester enhancement) were evaluated by chemical and sensory analysis.